THE INFLUENCE OF GARDEN ON PSYCHOLOGICAL COMFORT WITHIN THE HEALING ENVIRONMENT CONCEPT (CASE STUDY : ZAINOEL ABIDIN HOSPITAL PARK) - Meutia, Zya Dyena; yasnibar (Center for Environmental Studies, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Zainoel Abidin Hospital has implemented a garden surrounding its premises to promote comfort, aesthetics, and safety. One approach to creating comfort in a hospital environment is by organizing and managing the space in both functional and aesthetic ways. This study aims to explore the perceptions of hospital users regarding the influence of the garden on their psychological comfort, based on the concept of a healing environment. The object of this study is the garden at Zainoel Abidin Hospital, with informants consisting of 10 individuals, 5 patients and 5 visitors. The method used is qualitative descriptive, with data collection techniques including observation, interviews, and documentation. The results of the study, as seen from the interviews with garden users, indicate that the presence of a garden in the hospital provides greater benefits than merely enhancing aesthetic value. Informants noted that while some users found the garden calming and beneficial, others expressed discomfort due to inadequate facilities within the garden area.